The Problem of Private Under-investment in Innovation: A Policy Mind Map - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2008)
This paper reviews the major finance-related causes of private under-investment in innovation and the consequent alternative choices for public policy. The focus is on incentive-based arguments that address the problem of limited appropriability of new knowledge, and on the lacking access to external sources of finance caused by imperfections in the capital market. Drawing a policy mind map, which aims to enhance the mutual awareness and coordination of policy makers at the crossroads of technology and corporate finance, the paper is organised along the following chain of thought: causes and rationales, aims and targets, critical constraints, and the main finance-related instruments of innovation policy.
Keywords: 330; technological change; corporate finance; innovation policy; fiscal incentives; venture capital; Technischer Fortschritt; Unternehmensfinanzierung; Technologiepolitik; Anreiz; Risikokapital